Issues of Professionality and Competency of Islamic Religious Education Teachers in Facing the Society 5.0 Era - Nurdiyanto, Nurdiyanto; Thoriqul Islam, Muhammad; Marjany, Nawa; Maslani; Hasbiyallah (IAIN Ponorogo, 2024)
This research uncovers the Islamic religious education teachers’ professionalism and competence issues in the Society 5.0 era. The research employed the Systematic Literature Review method. Articles were obtained from national and international journals. Researchers chose 15 articles from hundreds of relevant articles in the last 5 years. Then, the researchers analyzed and tabulated the tabular data with the name of the researcher, year of publication, publisher, and research results. The research indicated that Islamic religious education teacher professionalism and competence were strongly supported by efforts to increase the education level, training, and teacher upgrading programs. In addition, teacher quality and professionalism needed to be improved through cluster activity centers, teacher working groups, and the Republic of Indonesia Teachers’ Association. It was also necessary to increase a work ethic based on service. The conclusion and implications of improving human resource competencies are developing students’ abilities. Ultimately, teachers will always be active and require self-regulation to overcome the industrial revolution toward a golden Indonesia in 2045.